SOSIALISASI PENANGANAN ANAK KECANDUAN SMARTPHONE DI GPIN BUKIT ZAITUN PANJANG - Rudy Roberto Walean; Setiaman Larosa; Serepina Hasibuan; Yoges Mahendra Saragih; Sorni Lami (Jurnal PKM Setiadharma, 2022)
The condition of children addicted to smartphones in this digital era is alarming. The same condition also occurs among the children and youth of GPIN Bukit Zaitun. This condition exacerbates the absence of the role of parents and Sunday school teachers in educating children in this digital era. Therefore, through this research, two things will be answered: first, how is the influence of parents and Sunday school teachers on the use of smartphones by children and adolescents? Second, how are the efforts of parents and Sunday school teachers in dealing with smartphone addiction children? This study uses quantitative methods with data collection techniques using questionnaires distributed to parents and Sunday school teachers at GPIN Bukit Zaitun, as well as providing socialization to understand the efforts that parents and Sunday school teachers can make. The data obtained found that parents and Sunday school teachers significantly influenced disciplining and approaching children and adolescents. From the socialization, it is also known that the solution that can increase the role of parents and Sunday school teachers is by counselling them with self-management methods and disciplining them.